BURDEN AMONG FAMILY CAREGIVERS OF ADVANCED-CANCER PATIENTS IN INDONESIA - Ike Wuri Winahyu Sari; Sri Warsini; Christantie Effendy (Belitung Raya Foundation, Indonesia, 2018)
Background: There have been various studies into the family caregivers’ experiences in taking care of advanced-cancer patients. But a study exploring the burden among family caregivers has not yet been conducted in Indonesia, a country which has strong family bonds among family members. Objective: This present study aimed to identify the burden among family caregivers of advanced cancer patients. Methods: This study was a cross-sectional study conducted from December 2016 to February 2017 on 178 consenting family caregivers and advanced cancer patients, selected using a purposive sampling technique. The Caregiver Reaction Assessment (CRA) was used to measure their burden. Data were analyzed using descriptive analyzes and bivariate analyzes. Results: The burden among family caregivers was 2.38 ± 0.38 (mean range 1-5). The highest burden was in the disrupted schedule domain. Conclusion: Our findings identified that the burden among family caregivers was at the medium level. The length of care per day and family support are potential targets for preventative intervention strategies to reduce the burden among the family caregivers.